Kegagalan Tata Kelola Korporat dan Dampaknya terhadap Kepercayaan Publik: Studi Literatur pada PT Asuransi Jiwasraya - A’isyah Hani Agustin; Safania Anindya; Rohmawati Kusumaningtias; Ambar Kusumaningsih (BADAN PENERBIT STIEPARI PRESS, 2025)
Failure of corporate governance in State-Owned Enterprises (SOEs) can have systemic impacts, including loss of public trust in state institutions. The case of PT Asuransi Jiwasraya is a clear example of how violations of Good Corporate Governance (GCG) principles can lead to major financial scandals. This research aims to analyze the causes of governance failure and its impact on public trust. The method used is a descriptive qualitative approach through a literature study of secondary sources such as scientific journals, official agency reports, and news from trusted media. The results showed that the failure was caused by weak internal and external supervision, unprudent investment management, and manipulation of financial statements. The scandal had a widespread impact on the decline of public trust in the financial industry and the credibility of the government. This research emphasizes the importance of comprehensive reform of SOE governance, strengthening the role of regulators, and improving public financial literacy as an effort to prevent similar cases in the future.